REKOGNISI FATWA DALAM PLURALISME HUKUM KELUARGA ISLAM INDONESIA “KAJIAN HUKUM ISLAM SUSTAINABLE” - Masnun, Masnun Tahir; Apipuddin, Apipuddin (Indonesian Association of Islamic Family Law Lecturers, 2020)
New problems that have arisen in this disruption era have inevitably influenced the law of family relations together with its dynamism which developed revolutionary. Moreover, they have demanded speedy and permanent solutions with a strong Sharia bases. As a product of Islamic law that is responsive and flexible, fatwa has a strategic role in renewal and sustainability of Islamic family law for every challenge in different era as well as being a dynamist in the pluralism of Indonesian Islamic family law implementations. The study of recognition of fatwa from authoritative circles is important to be considered since there has been the outbreak and shifting on Muslim communities’ interest on application-based fatwa products from non-authoritative circles.